The Effect of Mixed Liquor Administration on The Johnsen’s Score and The Number of Sertoli Cells and Leydig Cells on The Wistar Strain White Rats (Rattus norvegicus) - Aqidah Khariri1 , Anny Setijo Rahaju2,4, Arifa Mustika3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
To analyze the effect of mixed liquor administration on the Johnsen’s score and the number of Sertoli cellsand Leydig cells on the Wistar strain white rats (Rattus norvegicus). A total of 28 rats were divided into 4groups: C, P1, P2, and P3. Rats were given mixed liquor with different dose, namely P1 (1 ml), P2 (2 ml),and P3 (4 ml) each day for 14 days, then compared to C group which was given 4 ml of distilled water usingan oral gavage. Mixed liquor consists of 20% ethanol and 4% methanol. The histopathological features wereevaluated by the Johnsen’s score, the number of Sertoli cells, and Leydig cells in cross-sectional preparationof rat testicular tissue with 400× magnification. Datas were analyzed using the Kruskal-Wallis test and OneWay ANOVA test with a confidence level of p <0.05. The P3 group had the lowest Johnsen’s score and thenumber of Sertoli cells, 6.442±0.293 and 5.942±0.674, respectively. A significant decrease in increased doseoccurred in the Sertoli cell count but not in the Johnsen’s score. Group P2 had the lowest number of Leydigcells, 6.421±0.360. The administration of mixed liquor caused a decrease in Johnsen’s score and the numberof Sertoli cells and Leydig cells on the Wistar strain white rat (Rattus norvegicus).